The macro- and microelement provision of preschool children with psychomotor developmental disorders. Literature review and authors' research - S.L. Niankovskyy; A.I. Pyshnyk; O.V. Kuksenko; O.I. Hrushka (Zaslavsky O.Yu., 2021)
Background. An integral part of a child's physical and mental development is a balanced diet. Insufficient or inadequate for a child developing organism's needs nutrition in preschool age leads to a delay in physical, cognitive, and mental development. The study was aimed to assess the macro-and micronutrient provision status of preschool children with psychomotor developmental delay, identify the presence of macro- and micronutrient deficiencies, define the connection between macro- and micronutrient levels in patient's serum and psychomotor developmental disorders. Materials and methods. The study analyzed the results of biochemical blood tests of blood serum samples for total calcium, magnesium, and iron level in 30 preschool children with psychomotor developmental disorders. Results. Mental retardation was observed in 53.33 % of examined children, autism spectrum disorders - in 20 % of examined children; minimal brain dysfunction - in 13.33 %, attention deficit hyperactivity disorder (ADHD) - in 13.33 %. 93.33 % of examined children had a deficiency of total calcium, magnesium - in 63.33 %, iron - in 20 %. Ten percent of patients had a deficiency of both total calcium, magnesium, and iron; one child (3.33 %) had no deficits. The most common deficiency in almost all subgroups of examined children was a combined deficiency of total calcium and magnesium. Only in the minimal brain dysfunction subgroup, in 50 % of cases, there was a combined deficiency of total calcium and magnesium, and in other 50 % of cases - an isolated deficiency of total calcium. This study identified a reliable inverse correlation of moderate strength between the level of total calcium and psychomotor development disorders and between the level of magnesium and the hyperexcitability syndrome. This study detected a weak unreliable correlation between the levels of magnesium and neurological disorders; an inverse unreliable weak correlation was found between iron and psychomotor developmental disorders. Conclusions. The most common deficiency in almost all subgroups of examined children was a combined deficiency of total calcium and magnesium. This study identified a reliable inverse correlation of moderate strength between the level of total calcium and psychomotor developmental disorders and between the level of magnesium and the hyperexcitability syndrome. There is also a weak direct unreliable correlation between magnesium level and psychomotor disorders. An inverse unreliable weak correlation was detected between the concentration of iron and psychomotor disorders.